English as an additional language in the early years : linking theory to practice - Mistry, Malini; Sood, Krishan (London : New York : Routledge, 2015)
With the English as Additional Language (EAL) population growing rapidly, it is essential that settings and schools meet individual learner needs and provide an inclusive culture where different languages, cultures and religions are accepted and celebrated. Packed with essential information on key theories and best practice, and written in a highly readable style this book aims to raise awareness of main issues and offer practical support for practitioners working with children with EAL. Covering a wide range of topic such as new arrivals, working with parents, assessment, planning, resourcing, play, communication and language, each chapter clearly lays out the key concepts, ideas and strategies alongside examples of good practice. Encouraging a reflective approach, the book features: Checklists, diagrams, chapter objectives and summaries and suggestions for further reading Case studies to illustrate practice Reflective activities to develop critical thinking Challenging many assumptions and stereotypes about EAL learners, this invaluable text will support students and practitioners in meeting the individual needs of all the children in their care
Includes bibliographical references and index.
Keywords: Bilingualism in children; Second language acquisition; English language